RANCANG BANGUN APLIKASI MONITORING DAN EVALUASI KINERJA DIVISI KAPAL NIAGA BERDASARKAN METODE BALANCED SCORECARD PADA PT. PAL INDONESIA - Ibrahim, Yudana Malik; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
In an effort to repair the company PT. PAL changed the concept of performance appraisal of each division were previously more focused on the financial report into the performance appraisal with the concept of balanced scorecard, this is in line with the direction of the Ministry of SOEs as a state institution builder to each SOE. Merchant vessel division needs help to be able to ensure that the process goes according to plan and know how condition the object in the design, implementation and results. Based on the above issues authors propose Application Performance Monitoring and Evaluation Merchant Vessel Division. The author uses a balanced scorecard method in accordance with the concept of the PT. PAL. To process the existing data using the method of direct user rating. The data that has been processed will be the source of the data in the reports to be made. With the Application Performance Monitoring and Evaluation Merchant Vessel Division, the management can be easier to monitor and evaluate the performance of the Merchant Vessel Division. Thus the management can identify problems on the merchant vessel division in accordance with the concept of the balanced scorecard method